Synthesis of gamma-WO3 thin films by hot wire-CVD and investigation of its humidity sensing properties - Jadkar, Vijaya; Pawbake, Amit; Waykar, Ravindra; Jadhavar, Ashok; Date, Abhijit; Late, Dattatray; Pathan, Habib; Gosavi, Suresh; Jadkar, Sandesh (Physica Status Solidi A-Applications and Materials Science, 2017)
In this study, monoclinic tungsten oxide (gamma-WO3) have been grown in a single step using HW-CVD method by resistively heating W filaments in a constant O-2 pressure. The formation of gamma-WO3 was confirmed using low angle-XRD and Raman spectroscopy analysis. Low angle-XRD analysis revealed that as-deposited WO3 film are highly crystalline and the crystallites have preferred orientation along the (002) direction. HRTEM analysis and SAED pattern also show the highly crystalline nature of WO3 with d spacing of similar to 0.38 nm, having an orientation along the (002) direction. Surface topography investigated by SEM analysis shows the formation of a uniform and homogeneous cauliflower like morphology throughout the substrate surface without flaws and cracks. A humidity sensing device incorporating WO3 is also fabricated, which shows a maximum humidity sensitivity factor of similar to 3954% along with a response time of similar to 14 s and a recovery time of similar to 25 s. The obtained results demonstrate that it is possible to synthesize WO3 in a single step by HW-CVD method and to fabricate a humidity sensor by using it. (C) 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim

Solvothermal growth of PbBi2Se4 nano-flowers: a material for humidity sensor and photodetector applications - Aher, Rahul; Bhorde, Ajinkya; Nair, Shruthi; Borate, Haribhau; Pandharkar, Subhash; Naik, Dhirsing; Vairale, Priti; Karpe, Smita; Late, Dattatray; Prasad, Mohit; Jadkar, Sandesh (Physica Status Solidi A-Applications and Materials Science, 2019)
In the present work, lead bismuth selenide (PbBi2Se4) nano-flowers are synthesized by using a simple solvothermal method. Humidity sensor and photodetector based on PbBi2Se4 nano-flowers are fabricated on indium tin oxide (ITO) substrates and their sensing properties are investigated. Formation of PbBi2Se4 is confirmed by XRD, EDS, and XPS whereas formation of nano-flowers is confirmed by SEM and TEM analysis. XRD analysis reveals the hexagonal crystal structure of PbBi2Se4 phase with a = b = 4.22 angstrom, and c= 17.42 angstrom. The surface morphology of PbBi2Se4 clearly shows the formation of well-organized flower-like nanostructures which closely resembles the shape of Dahlia. The elemental mapping of chemical constituents obtained from SEM-EDS analysis shows uniform distribution of chemical constituents for the Pb, Bi, and Se in PbBi2Se4 nano-flowers. The PbBi2Se4 nano-flowers based humidity sensor has a typical response time of approximate to 65s and recovery time of approximate to 75 s. In case of PbBi2Se4 nano-flowers-based photodetector, the response and recovery time are observed approximate to 121 and approximate to 123 s, respectively, under visible light illumination with photoresponsivity (5 x 10(-6)), photosensitivity (2.16%), and quantum efficiency (1.5 x 10(4)). The obtained results demonstrate the potential applications of solvothermally grown PbBi2Se4 nano-flowers-based devices for humidity sensors and photodetectors. The ease of the present work is to develop novel material to obtain device quality humidity sensors and photodetectors.
Keywords: humidity sensor; PbBi2Se4; photodetector; XPS; XRD